Electronic properties, hydrogen bonding, stacking, and cation binding of DNA and RNA bases - Sponer, J; Leszczynski, J; Hobza, P (Biopolymers, 2001)
This review summarizes results concerning molecular interactions of nucleic acid bases as revealed by advanced ab initio quantum chemical (QM) calculations published in last few years. We first explain advantages and limitations of modern QM calculations of nucleobases and provide a brief history of this still rather new field. Then we provide an overview of key electronic properties of standard and selected modified nucleobases, such as their charge distributions, dipole moments, polarizabilities, proton affinities, tautomeric equilibria, and amino group hybridization. Then we continue with hydrogen bonding of nucleobases, by analyzing energetics of standard base pairs, mismatched base pairs, thio-base pairs, and others. After this, the nature of aromatic stacking interactions is explained. Also, nonclassical interactions in nucleic acids such as interstrand bifurcated hydrogen bonds, interstrand close amino group contacts, C [bond] H...O interbase contacts, sugar-base stacking, intrinsically nonplanar base pairs, out-of-plane hydrogen bonds, and amino-acceptor interactions are commented on. Finally, we overview recent calculations on interactions between nucleic acid bases and metal cations. These studies deal with effects of cation binding on the strength of base pairs, analysis of specific differences among cations, such as the difference between zinc and magnesium, the influence of metalation on protonation and tautomeric equlibria of bases, and cation-pi interactions involving nucleobases. In this review, we do not provide methodological details, as these can be found in our preceding reviews. The interrelation between advanced QM approaches and classical molecular dynamics simulations is briefly discussed.
Keywords: molekulární modely; DNA; Electrons; Cations; Models, Molecular; Static Electricity; konformace nukleové kyseliny; elektrony; Nucleic Acid Conformation; vodíková vazba; RNA; Hydrogen Bonding; kationty; statická elektřina